Treatment agent for carbon fiber precursor and method for producing carbon fiber bundle using said treatment agent for carbon fiber precursor
The use of an amino-modified silicone and polydimethylsiloxane emulsion with a nonionic surfactant addresses fiber fusion and adhesion issues, enhancing oil pickup and reducing burn spots, leading to improved carbon fiber production.
Patent Information
- Application Number
- JP2021139255
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-27
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-08-27
AI Technical Summary
Existing carbon fiber precursor treatment agents fail to effectively prevent fusion and adhesion between fibers, leading to uneven physical properties and reduced strength, while also lacking optimal oil pickup properties and stability.
A treatment agent comprising an amino-modified silicone, polydimethylsiloxane, and a nonionic surfactant in a specific ratio, forming an oil-in-water emulsion, which suppresses adhesion and fusion, enhances oil pickup, and reduces burn spots during the flame-retardant process.
The treatment agent effectively prevents fiber fusion and adhesion, maintains uniform physical properties, improves oil pickup efficiency, and reduces burn spots, resulting in high-quality carbon fibers with enhanced production efficiency.
Smart Images

Figure 0007602983000005 
Figure 0007602983000001 
Figure 0007602983000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a treating agent for carbon fiber precursors, a method for producing a carbon fiber bundle using the treating agent for carbon fiber precursors, and a method for reducing burn spots on a carbon fiber precursor using the treating agent for carbon fiber precursors. [Background technology]
[0002] Carbon fibers have higher specific strength and specific modulus than other fibers, and therefore are being widely deployed as reinforcing fibers for composite materials in a wide range of applications, including sports, aerospace, automobiles, civil engineering and construction, pressure vessels, general industrial applications such as wind turbine blades, and heat dissipation components for electronic devices. In particular, there is a high demand for even higher strength and modulus in sports and aerospace applications.
[0003] For example, polyacrylonitrile carbon fibers, which are the most widely used of carbon fibers, are industrially produced through a spinning process in which a raw material polymer such as an acrylic resin is spinned to obtain a polyacrylonitrile fiber bundle, which is a carbon fiber precursor; a flame retardant process in which the polyacrylonitrile fiber bundle is converted into a flame retardant fiber in an oxidizing atmosphere at 200 to 400°C; a carbonization process in which the fiber is carbonized in an inert atmosphere at at least 1000°C; and, if necessary, a graphitization process in which the fiber is graphitized at about 2000°C or higher. In the spinning process, polyacrylonitrile resin is extruded from a nozzle with many fine holes to form fibers, which are then washed with water and stretched for the first time. An oil agent (also known as a treatment agent for carbon fiber precursors) is applied and the fibers are dried, and then stretched for the second time. In the flame-retarding process, the polyacrylonitrile fiber bundle obtained in the spinning process is flame-retarded by heat treatment.
[0004] If adhesion occurs between fibers during the flame-retardant process, problems such as fuzzing and thread breakage will occur in the subsequent carbonization process. It is known that adhesion between fibers can occur in two ways: fusion and agglutination. Fusion is a phenomenon in which fibers melt and stick together. Agglutination is a phenomenon in which the oil undergoes a cross-linking reaction when heated, causing it to become highly viscous and solidify, and multiple fibers are fixed there. If fusion or agglutination occurs, the progress of flame-retardant and carbonization will be uneven, which can lead to a decrease in the physical properties of the carbon fiber. As a method for preventing this fusion or sticking between fibers, various methods have been investigated, such as applying various silicone-based treating agents for carbon fiber precursors to the fibers.
[0005] For example, Patent Document 1 discloses a method of applying an amino-modified silicone-based treatment agent to a precursor, which is a precursor of carbon fibers, to prevent the precursor from sticking and to prevent the carbon fibers from fusing, and the treatment agent can further improve heat resistance by a crosslinking reaction caused by heat. However, according to the method disclosed in Patent Document 1, if a crosslinking reaction of an amino-modified silicone-based treating agent, which has good thermal crosslinking properties, occurs on the fibers in the heat treatment step to form a film, the treating agent cannot migrate into the fiber bundle in the flame retardant treatment step, causing fusion between the single fibers, which can easily lead to problems such as a decrease in the strength of the carbon fibers.
[0006] Patent Document 2 discloses a method for suppressing adhesion and fusion between fibers by using a treatment agent for carbon fiber precursors that contains polyether-modified silicone. However, according to the method disclosed in Patent Document 2, catalysts such as platinum used in synthesizing the polyether-modified silicone and unreacted raw material polyether are mixed into the treating agent as impurities, resulting in problems such as large fluctuations in the quality of the treating agent and unstable physical properties of the carbon fiber. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2002-129481 A [Patent Document 2] Patent No. 6488104 Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above, there is a need for a method for suppressing the fusion and sticking of carbon fiber precursors.
[0009] Incidentally, the oil agent as a treatment agent for carbon fiber precursors is applied to the fiber bundle in the form of an emulsion type in which the oil agent composition is emulsified and used, a solvent type in which the oil agent composition is dissolved in a solvent and used, or a neat type in which the oil agent composition is used as it is. With emulsion-type oil agents, the oil agent is applied to the fiber bundle by immersing it in a tank containing the emulsion, and the fiber bundle with the oil agent applied is squeezed with rollers to remove excess oil agent. Here, it is desired that the oil agent adheres well to the fiber bundle immersed in the tank (oil pickup). With high oil pickup, the oil agent in the oil agent emulsion adheres to the fiber bundle efficiently and is quickly consumed, and unused oil agent emulsion is newly added to the tank. If the oil agent emulsion in the tank can be refreshed quickly in this way, it is possible to reduce the phenomenon that the emulsion remaining in the tank breaks down and the oil agent separates over time, the oil agent components denature, oil adheres to the inner wall of the tank, and gel accumulates. However, a treating agent for carbon fiber precursors that can reduce adhesion between fibers and improve oil pick-up properties has not been known so far. Therefore, the present invention aims to provide a treatment agent for carbon fiber precursors that can reduce fusion and sticking between carbon fiber precursors. Another object of the present invention is to provide a treatment agent that can obtain carbon fibers with excellent oil pick-up properties and uniform physical properties. [Means for solving the problem]
[0010] The present inventors have discovered that the problems of the present invention can be solved by blending a polydimethylsiloxane having a SiOH group / Si(CH3)3 ratio at the molecular chain end within a specified range in a treatment agent for carbon fiber precursors, which is an oil-in-water silicone emulsion composition containing an amino-modified silicone and a surfactant, and have thus completed the present invention.
[0011] That is, the present invention provides (A) amino-modified silicone; (B) Kinematic viscosity at 25°C is 5 to 500 mm 2 / s, and a ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals is 3 / 97 to 100 / 0; (C) a surfactant; (D) water, The content of the component (B) relative to 100 parts by mass of the component (A) is 0.1 parts by mass or more and 10 parts by mass or less, and the treating agent for carbon fiber precursors is an oil-in-water silicone emulsion composition. Effect of the Invention
[0012] The treating agent for carbon fiber precursors of the present invention is useful as an oil-in-water silicone emulsion composition that inhibits adhesion between carbon fiber precursors and also has excellent oil pick-up properties. [Brief description of the drawings]
[0013] [Figure 1] DTG graph showing the combustion peak. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The treating agent for carbon fiber precursors, the method for producing a carbon fiber bundle using the treating agent for carbon fiber precursors, and the method for reducing burn spots on carbon fiber precursors according to the present invention will be described in detail below.
[0015] The treating agent for carbon fiber precursor according to the present invention is (A) amino-modified silicone; (B) Kinematic viscosity at 25°C is 5 to 500 mm 2 / s, and a ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals is 3 / 97 to 100 / 0; (C) a surfactant; (D) water, The oil-in-water silicone emulsion composition is characterized in that the content of the component (B) is from 0.1 to 10 parts by mass per 100 parts by mass of the component (A).
[0016] The structure of the amino-modified silicone (A) is not particularly limited, and may be linear, branched, or cyclic. That is, the amino group, which is the modifying group, may be bonded to the side chain of the silicone, which is the main chain, or may be bonded to the terminal, or may be bonded to both. The amino group may be of the monoamine type or polyamine type, and both may coexist in one molecule. The amino-modified silicone (A) may be one type, or may be a mixture of two or more types of amino-modified silicones. The amino-modified silicone may, for example, be a compound represented by the following general formula (1): [ka]
[0017] In formula (1), R 1 ~R 6 are either the same or different monovalent saturated or unsaturated hydrocarbon functional groups having 1 to 14 carbon atoms, hydroxyl groups, nitrogen-containing groups, sulfur-containing groups, or hydrogen. p and q are both any integer of 1 or more. R 1 ~R 6 At least one of R in formula (1) is a nitrogen-containing group. 1 ~R 6 may be the same or different.
[0018] In the above formula (1), R 1 ~R 6When is a nitrogen-containing group, the nitrogen-containing group can be specifically represented by the following general formula (2).
[0019] [ka]
[0020] In formula (2), R 9 ~R 10 is a saturated hydrocarbon group having 1 to 5 carbon atoms, and R 11 ~R 12 is hydrogen or a saturated hydrocarbon group having 1 to 10 carbon atoms, which is linear, branched or cyclic. t is an integer satisfying either 0 or 1, but is preferably 1 from the viewpoint of production of the composition. Examples of functional groups satisfying this condition include -CH2-CH2-CH2-NH(CH3), -CH2-CH2-CH2-N(CH3)2, -CH2-CH2-NH-CH2-CH2-NH2, -CH2-CH2-CH2-NH(CH3), -CH2-CH2-CH2-NH-CH2-CH2-NH2, -CH2-CH2-CH2-NH-CH2-CH2-NH-CH2-CH2-N(CH3)2, -CH2-CH2-CH2-NH-CH2-CH2-NH(CH2CH3), -CH2-CH2-CH2-NH-CH2-CH2-N(CH2CH3)2, -CH2-CH2-CH2-NH-CH2-CH2-NH(cyclo-CH 11 ), etc.
[0021] In the above-mentioned carbon fiber precursor treating agent, the (A) amino-modified silicone may contain 3% or more of an amino-modified silicone having a SiOH group or a SiOCH3 group at at least one molecular chain end.
[0022] The SiOH or SiOCH3 groups at the ends of the molecular chains bond the components (A) together, polymerizing (gelling) and forming a protective coating on the surface of the carbon fiber. While the protective coating has a fusion-preventing effect, if the ratio of SiOH or SiOH3 groups is too high, sticking tends to occur. If the ratio of SiOH or SiOCH3 groups is too low, the fusion-preventing effect becomes insufficient.
[0023] Due to this mechanism, the lower limit of the content of the amino-modified silicone having at least one SiOH group or SiOH3 group at the molecular chain end relative to the total amount of the amino-modified silicone (A) is 3%, preferably 10%, and more preferably 15%. The SiOH group or SiOH3 group at the molecular chain end contributes to gelation as a crosslinking point of the (A) component, so the higher the ratio, the higher the anti-fusing effect. If it is within the above range, a high anti-fusing effect can be obtained. The upper limit of the content of the amino-modified silicone having a SiOH group or a SiOH3 group at at least one molecular chain terminal relative to the total amount of (A) amino-modified silicone is 100%, preferably 90%, and more preferably 70%. Within the above range, sticking problems caused by gelation proceeding too quickly can be avoided.
[0024] The lower limit of the kinetic viscosity of the amino-modified silicone (A) at 25°C is not particularly limited, but is preferably 20 mm 2 / s or more, preferably 50 mm 2 The upper limit of the kinetic viscosity of the amino-modified silicone at 25° C. is not particularly limited, but is preferably 40,000 mm 2 / s or less, more preferably 20000 mm 2 If the kinetic viscosity is within the above range, the stability of the emulsion is increased.
[0025] The polydimethylsiloxane in component (B) according to the present invention is Dimethylpolysiloxane, in which all the side chains and terminals of the polysiloxane are methyl groups, and This refers to dimethylpolysiloxane in which at least a part of the molecular chain terminals of the dimethylpolysiloxane is a SiOH group. Component (B) may be linear, branched, or linear or branched with a cyclic structure in part of the molecular chain. It may be a single component or a mixture of these. Polydimethylsiloxanes may be used alone or in combination of two or more kinds. Polydimethylsiloxanes in which the molecular chain terminals are methyl groups and polydimethylsiloxanes in which the molecular chain terminals are SiOH groups may be appropriately mixed and used. The type of polydimethylsiloxane is not particularly limited, and any known polydimethylsiloxane can be appropriately used.
[0026] Furthermore, the kinetic viscosity of component (B) at 25°C is 5 mm 2 / s or more 500 mm 2 / s or less. 2 At or below 500 mm / s, the adsorption of these components to the carbon fiber precursor is extremely low, resulting in a decrease in oil pickup. 2 At above 1 / s, the emulsion stability of the carbon fiber precursor treatment agent is impaired.
[0027] The lower limit of the dynamic viscosity of polydimethylsiloxane at 25°C is 5mm 2 / s or more, preferably 10 mm 2 The upper limit of the dynamic viscosity of polydimethylsiloxane at 25°C is 500mm 2 / s or less, preferably 300 mm 2 By defining the kinetic viscosity within this range, the oil pick-up effect is further improved.
[0028] The polydimethylsiloxane (B) in the present invention has a ratio of SiOH groups / Si(CH3)3 at molecular chain terminals in the range of 3 / 97 to 100 / 0, preferably 10 / 90 to 90 / 10, and more preferably 15 / 85 to 70 / 30.
[0029] If all of the molecular chain ends of component (B) are methyl groups, there is little reaction between components (A) and (B), resulting in a low gelation prevention effect. Furthermore, components (A) and (B) are poorly compatible, so separation of the components is likely to occur, and the lubricating effect of the gel derived from component (A) cannot be obtained. In the end, the effect of reducing sticking by mixing components (A) and (B) is unlikely to be apparent. To obtain a high sticking reduction effect, it is necessary to convert part of the molecular chain terminals of component (B) into OH groups. The terminal OH groups of component (B) are highly reactive with component (A) and act to prevent gelation. In addition, the presence of OH groups at some of the terminals improves compatibility with component (A), and increases the lubricity of the gel when it forms from component (A) during the flame-resistant process. In view of this, the ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals of component (B) is in the range of 3 / 97 to 100 / 0, preferably 10 / 90 to 90 / 10, and more preferably 15 / 85 to 70 / 30. The higher the SiOH ratio at the molecular chain end, the greater the effect of reducing sticking, and the lower the SiOH ratio, the greater the suppression of polydimethylsiloxane reactivity, which tends to increase the stability over time (emulsion stability) of the treatment agent. The mechanism behind this can be explained as follows.
[0030] If component (B) is a fully blocked polydimethylsiloxane in which all molecular chain terminals are methyl groups, the interaction with component (A) will be weak, resulting in the existence of two separate phases: component (A) which is prone to gelation, and the terminal-blocked polydimethylsiloxane which is resistant to gelation. In this case, the effect of inhibiting gelation will be insufficient, and sticking caused by component (A) will be more likely to occur. If a polydimethylsiloxane having a ratio of SiOH groups / Si(CH3)3 of at least 3 / 97 at the molecular chain ends is used as component (B), the compatibility between components (A) and (B) is increased, making it difficult for phase separation to occur, and as a result, it is possible to suppress sticking. The lower limit of the ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals of component (B) is 3 / 97, preferably 10 / 90, and more preferably 20 / 80. The higher the ratio of SiOH groups, the higher the compatibility with component (A) and the greater the sticking suppression effect.
[0031] (A) Amino-modified silicone has a higher adsorption to carbon fiber precursors than polydimethylsiloxane, and therefore contributes to the lubrication of the carbon fiber precursors, and works effectively as a lubricant during yarn feeding. In addition, amino-modified silicone has a higher film-forming property due to a crosslinking reaction when heated than polydimethylsiloxane, and therefore is more likely to form a protective film on the surface of the carbon fiber precursor, and is the main component for suppressing fusion between carbon fiber precursors. (B) Polydimethylsiloxane contributes to balancing the oil pickup property of the carbon fiber precursor treatment agent and the suppression of adhesion between fibers. More details are as follows.
[0032] Component (B), which is unmodified silicone, has low adsorption to carbon fiber precursors such as polyacrylonitrile (hereinafter also referred to as PAN), which can be explained by the fact that carbon fiber precursors have a high solubility parameter, while silicones tend to have a low solubility parameter. Therefore, by combining component (B), which is unmodified silicone, with component (A), which is modified with amino groups that have good adsorption to carbon fiber precursors, it is possible to increase the adsorption to carbon fiber precursors. When a mixture of (A) amino-modified silicone and (B) polydimethylsiloxane is applied to a carbon fiber precursor, it is believed that component (A) is preferentially adsorbed onto the surface of the carbon fiber precursor, and that the molecular chains of component (B) are further adsorbed in such a way that they become entangled with the molecular chains of component (A). Therefore, if the compounding ratio of component (B) to component (A) exceeds the above range (i.e., the ratio of component (B) exceeds 10 parts by mass per 100 parts by mass of component (A)), the oil pickup property decreases. In addition, since the proportion of amino-modified silicone (A) decreases, the amino-modified silicone cannot fully exert its inherent function of suppressing fusion.
[0033] When (A) amino-modified silicone is heated, it transforms into a gel through a cross-linking reaction using amino groups and terminal SiOH groups. When it is adsorbed onto carbon fiber precursors, this gel functions as a protective film and prevents the carbon fiber precursors from fusing together. However, since the resulting gel is sticky, if the gelation proceeds too quickly it can cause the carbon fiber precursors to stick together. Adding component (B) to component (A) reduces sticking through the following mechanism. Therefore, when the compounding ratio of component (B) to component (A) is below the above range (i.e., the range of less than 0.1 part by mass of component (B) per 100 parts by mass of component (A)), sticking becomes a problem.
[0034] In this regard, when the blending amount of the (B) component per 100 parts by mass of the (A) component is 0.1 part by mass or more and 10 parts by mass or less, the anti-fusion effect of the (A) component can be fully exerted, while sticking due to gelation of the (A) component can be suppressed, and further, the oil pickup property can be maintained at a sufficiently high level.
[0035] The mechanism by which adhesion is reduced by mixing components (A) and (B) is as follows. During the flame-proofing process, mechanical stimuli (contact with rollers and vibrations caused by hot air) are constantly being applied, so if the gelation proceeds slowly, even if multiple fibers are temporarily bound by the gel, this can be resolved spontaneously. However, if the gelation proceeds rapidly, the gel will harden before the binding is released, causing agglutination. In mixed silicones that contain component (B) in addition to component (A), some of the reactive sites of component (A), such as the amino groups and terminal SiOH groups, are used to react with component (B). Component (B) only has a few reactive sites in its molecule (i.e., SiOH groups at the ends of the molecular chain), and its crosslinking ability is far inferior to that of component (A). Therefore, when components (A) and (B) are mixed, the gelation process proceeds more slowly. At the same time, unreacted component (B) exists near the surface of the gel that is formed as a lubricating oil, reducing the stickiness of the gel.
[0036] If the content of the (B) component relative to the (A) component is too small, the gelation of the carbon fiber precursor treatment agent is accelerated, and sticking is likely to occur. Therefore, the lower limit of the amount of the (B) component relative to 100 parts by mass of the (A) component is 0.1 parts by mass, preferably 0.3 parts by mass, and more preferably 0.5 parts by mass.
[0037] If the content of the (B) component relative to the (A) component is too high, the (B) component has low adsorption to the carbon fiber precursor, so that the carbon fiber precursor treatment agent cannot cover the carbon fiber precursor evenly, and fusion is likely to occur. At the same time, the oil pickup property is also reduced. Therefore, the upper limit of the amount of the (B) component relative to 100 parts by mass of the (A) component is 10 parts by mass, preferably 7.5 parts by mass, and more preferably 5.0 parts by mass.
[0038] The (C) surfactant in the present invention may be any of a variety of known substances, and may be appropriately selected depending on the properties of the (A) and (B) components and the properties of the required emulsion composition. The (C) surfactant may be a cationic surfactant, a nonionic surfactant, an anionic surfactant, or a mixture thereof.
[0039] In the above-mentioned carbon fiber precursor treating agent, the surfactant (C) is particularly preferably a nonionic surfactant. When a nonionic surfactant is used as the surfactant, even if the component (A) and / or the component (B) have a high viscosity, the component can be handled as a low-viscosity liquid (low-viscosity emulsion composition) after emulsification, and therefore it becomes possible to adhere the component more uniformly to the carbon fiber precursor. In addition, there is an advantage that the component can be easily washed off even if it adheres to the equipment or the operator who processes the carbon fiber precursor.
[0040] Furthermore, a silicone emulsion composition in which components (A) and (B) are blended in a specified ratio and a nonionic surfactant is used as component (C) has the characteristic that it is easy to apply uniformly to the surface of the carbon fiber precursor, which has the advantage of reducing burnt spots that occur in the length direction of the carbon fiber precursor. In addition, if a nonionic surfactant having a polyoxyalkylene structure is used as component (C), the polyoxyalkylene portion will generate peroxide through autoxidation when heated, promoting the flame resistance of the carbon fiber precursor. Since the molecules of this peroxide are small, the peroxide can easily penetrate into the interior of the carbon fiber precursor, making it possible to reduce uneven sintering that occurs inside and outside the single fiber.
[0041] Generally, methods for reducing burn spots on carbon fiber precursors include (1) gradually carrying out flame-retardant treatment over a long period of time, and (2) blending an exothermic material such as itaconic acid into the carbon fiber precursor itself. However, method (1) requires a low treatment temperature, which results in a problem of longer process time and reduced productivity. Method (2) can solve this problem, but its effectiveness cannot be said to be sufficient. However, according to the present invention, as described above, it is possible to reduce burn spots in both the length direction of the fibers and the inward direction of the fibers.
[0042] Examples of nonionic surfactants include polyethylene glycol-type nonionic surfactants such as higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, aliphatic ethylene oxide adducts, polyhydric alcohol aliphatic ester ethylene oxide adducts, higher alkylamine ethylene oxide adducts, aliphatic amide ethylene oxide adducts, ethylene oxide adducts of oils and fats, and polypropylene glycol ethylene oxide adducts; and polyhydric alcohol-type nonionic surfactants such as aliphatic esters of glycerol, aliphatic esters of pentaerythritol, aliphatic esters of sorbitol, aliphatic esters of sorbitan, aliphatic esters of sucrose, alkyl ethers of polyhydric alcohols, and fatty acid amides of alkanolamines. These nonionic surfactants may be used alone or in combination of two or more kinds.
[0043] In the above-mentioned carbon fiber precursor treating agent, a combustion peak may be 180° C. or higher and 270° C. or lower in a differential thermogravimetric curve (DTG) obtained by time-differentiating a thermogravimetric curve of 1 mg of a sample of the carbon fiber precursor treating agent dried at a temperature of 105° C. for 3 hours and heating the sample at a rate of 5° C. / min with air circulation of 200 ml / min. The combustion peak temperature may be within the above range, and is more preferably 210° C. or higher and 245° C. or lower.
[0044] The sample on which the thermogravimetric analysis was carried out to determine the combustion peak was a treatment agent for carbon fiber precursors, which is an oil-in-water silicone emulsion composition, dried under heating conditions.
[0045] The carbon fiber precursor treating agent is also preferably adjusted so that the (C) surfactant is a nonionic surfactant having a polyoxyalkylene structure, and the average number of moles of oxyalkylene groups added by the (C) surfactant is adjusted so that the combustion peak in a differential thermogravimetric curve (DTG) obtained by time-differentiating a weight loss curve when 1 mg of a sample obtained by drying the carbon fiber precursor treating agent at a temperature of 105°C for 3 hours is heated at 5°C / min with air circulation of 200 ml / min is adjusted to be in the range of -30°C or more +20°C or less, more preferably -20°C or more -5°C or less, relative to a preset carbon fiber precursor treating temperature. If the range is -30°C or more +20°C or less, it is possible to suppress burn spots, and if the range is -20°C or more -5°C or less, the suppression effect is even more remarkable.
[0046] The present invention also relates to a composition comprising (A) an amino-modified silicone and (B) a polymerizable composition having a kinetic viscosity at 25° C. of 5 to 500 mm 2The carbon fiber precursor treating agent is an oil-in-water silicone emulsion composition comprising polydimethylsiloxane having a SiOH group / Si(CH3)3 ratio at molecular chain terminals of 3 / 97 to 100 / 0 at a molecular chain end temperature of 1 / s, (C) a nonionic surfactant, and (D) water. The carbon fiber precursor treating agent is an oil-in-water silicone emulsion composition comprising polydimethylsiloxane having a SiOH group / Si(CH3)3 ratio at molecular chain terminals of 3 / 97 to 100 / 0 at a molecular chain end temperature of 1 / s, (C) a nonionic surfactant, and (D) water. The carbon fiber precursor treating agent is an oil-in-water silicone emulsion composition comprising polydimethylsiloxane having a SiOH group / Si(CH3)3 ratio at molecular chain end ...
[0047] If the treatment agent for carbon fiber precursor contains the components (A), (B), and (C) and has a combustion peak temperature in DTG within the above range, it is possible to reduce burn spots on the carbon fiber precursor during the flame retardant treatment process. Here, the peak combustion temperature refers to T0 when the range of 150°C to 300°C of the DTG (a plot of the temperature derivative (Derivative TG) of the thermogravimetric curve against temperature T) is fitted with a function (Equation 1).
[0048]
number
[0049] For example, when the variables h, T0, and w are determined for the following composition according to a known method, the following values are obtained. Amino silicone: kinematic viscosity 200mm 2 / s, amino equivalent 4000, terminal OH ratio 25%, 83 mass parts, Polydimethylsiloxane: Dynamic viscosity 20mm 2 / s, terminal OH rate 25%, 2 parts by mass, Surfactant: C 12 H 25 -O-(C2H4O) 10 -(C3H6O)4H 15 parts by mass Water: The remainder obtained by subtracting the total mass of the above three components from 100 h=110(μg / min) T0 = 285 (℃) w=40(℃)
[0050] In the thermogravimetric analysis, about 1 mg of a sample is placed on an aluminum sample dish and placed in a thermogravimetric analyzer (e.g., Hitachi High-Tech Science EXSTAR 7000 Series TG / DTA 7300), and the temperature is raised from room temperature to 350°C at a heating rate of 5°C / min, and the thermogravimetric curve (TG) of the sample is measured. The obtained TG is differentiated with respect to temperature to obtain a differential thermogravimetric curve (DTG) (the horizontal axis is temperature (°C) and the vertical axis is DTG (μg / min)). The T0 when the range from 150°C to 300°C is fitted with a function (Equation 1) is defined as the combustion peak temperature. In the carbon fiber precursor treatment agent of the present invention, it is sufficient that this combustion peak temperature (for example, the temperature at the apex of the fitting curve in FIG. 1) is within the range specified in the present invention. In the carbon fiber precursor treating agent having the composition used in the present invention, the combustion peak observed in the vicinity of 200° C. to 300° C. is due to the autoxidation of the surfactant. The decomposition of silicone is seen as a peak at 350° C. or higher.
[0051] The purpose of the flame-proofing process is to oxidize and cyclize the carbon fiber precursor, which requires an oxidizing agent and thermal energy. In general, oxygen in the air is used as the oxidizing agent, and the power source of the flame-proofing furnace is used as the source of thermal energy. In the flame-proofing process, a temperature close to the thermal decomposition temperature of polyacrylonitrile, the main component of the carbon fiber precursor, is usually used. This thermal decomposition is a reaction that generates a large amount of heat, and once thermal decomposition begins, it has been observed that the temperature of the polyacrylonitrile sample can even become 30°C higher than the ambient temperature (Tatsuya Mita, "Research on the Thermal Decomposition of Polymers by Thermal Analysis - Focusing on the Example of Polyacrylonitrile -", Heat Measurement, 1975, Vol. 2 (3), p. 69). Therefore, when thermal decomposition begins in a part of the carbon fiber precursor during the flame-proofing process, localized thermal runaway can occur due to the heat generated by the carbon fiber precursor itself. Thermal runaway is likely to cause sintering spots in the carbon fiber precursor, and if it goes too far, the carbon fiber precursor will melt and fuse with the surrounding carbon fiber precursor, and in the worst case, the carbon fiber precursor will burn out and break. Therefore, it is important to find some way to stop the thermal runaway of the carbon fiber precursor.
[0052] When the (C) surfactant is heated, it undergoes an autoxidation reaction, generating peroxides. The generated peroxides are oxidizing agents, and are expected to oxidize the carbon fiber precursor in parallel with the oxygen supplied from the atmosphere, accelerating the flame-resistant process. Considering the autoxidation reaction in more detail, it is worth noting that an activation barrier must exist for the autoxidation reaction to occur. In other words, in order for the autoxidation reaction to occur, the (C) surfactant must absorb the thermal energy of the surroundings as a first step. In other words, in the autoxidation of the (C) surfactant, heat absorption occurs first in an amount that exceeds the activation barrier, and then peroxides are generated.
[0053] Now, considering the situation in which the carbon fiber precursor to which the oil has been applied proceeds to the flame-retardant process, the above-mentioned processes, namely, (C) the sudden heat generation due to the thermal decomposition of the carbon fiber precursor, (D) the temporary heat absorption due to the autoxidation reaction of the surfactant, and (E) the oxidation and cyclization of the carbon fiber precursor by the peroxides produced by the autoxidation reaction of the surfactant, are competing with each other.
[0054] When excessive heat is generated locally due to the heat generation caused by the thermal decomposition of the carbon fiber precursor, part of the heat is consumed to cause the autoxidation reaction of the surfactant (C), which cools the carbon fiber precursor and acts to suppress thermal runaway. In other words, in the stage of generating peroxides, the surfactant generates heat, but since the heat has no direction, it diffuses throughout the system. In general, the autoxidation of the surfactant catches the ends of the thermal runaway of the carbon fiber precursor and disperses the heat in all directions, thus stopping the thermal runaway.
[0055] The inventors have focused on this point and found that the optimal blending for reducing burn spots is required from the relationship with the combustion peak temperature obtained from the DTG curve of the oil agent. Conventionally, it was not possible to confirm the effect on burn spots unless a silicone component (which may be a single component or a mixture of multiple silicones) that can be effective was identified from various silicones, a surfactant that can stably emulsify the silicone component was also searched for, and the emulsion obtained after optimizing the emulsification conditions and emulsification method was actually applied to a carbon fiber precursor and heated. However, according to the present invention, a formulation that can reduce burn spots can be obtained by simply mixing small amounts of the (A) to (D) components and measuring the thermogravimetry without optimizing the emulsification conditions, which leads to a significant reduction in development time and cost. If the combustion peak temperature is within the above range, it can be confirmed that the endothermic and exothermic heat of the carbon fiber precursor treatment agent is balanced and the occurrence of burn spots is suppressed. A mixture of components (A) to (D) may be used to measure the peak combustion temperature, but for further simplification, components (A) to (C) other than water may be mixed without emulsification and thermogravimetric measurement may be performed. In this case, the mixing ratio of each component (A), (B), and (C) must be the same as the mixing ratio of each component when preparing the emulsion composition.
[0056] The mechanism of the reduction in the combustion peak temperature and burn spots can be explained as follows. The carbon fiber precursor treatment agent absorbs heat energy from the environment in an amount equivalent to the activation energy required for the autoxidation reaction, and then generates heat in a temperature range approximately equal to the combustion peak. When the combustion peak temperature is close to the carbon fiber precursor treatment temperature in the flame-resistant process (when the combustion peak temperature is 180°C or more and 270°C or less, or when the difference with the treatment temperature is -30°C or more and +20°C or less), the exothermic reaction of the carbon fiber precursor treatment agent proceeds slowly, so it does not promote burn spots. In addition, the fact that the combustion peak is close to the treatment temperature means that the reaction rate of the autoxidation of the surfactant is strongly dependent on temperature, and the autoxidation reaction is promoted when the temperature rises. Therefore, when thermal runaway occurs due to the thermal decomposition reaction of the carbon fiber precursor, the carbon fiber precursor treatment agent absorbs the excess heat generated locally on the surface of the carbon fiber precursor and diffuses it to a wide peripheral area, so that burn spots can be prevented.
[0057] When the combustion peak of the carbon fiber precursor treatment agent containing the components (A) to (D) is at a relatively low temperature (for example, a temperature lower than 180°C or a temperature 30°C or more lower than an arbitrarily set carbon fiber precursor treatment temperature), the carbon fiber precursor treatment agent is exposed to a high carbon fiber precursor treatment temperature in the flame retardant treatment step, causing rapid autoxidation. In this case, the peroxides generated all at once from the oil agent are likely to cause burn spots on the carbon fiber precursor.
[0058] On the other hand, when the combustion peak is at a relatively high temperature (for example, a temperature exceeding 270°C or a temperature higher than an arbitrarily set carbon fiber precursor treatment temperature + 20°C), autoxidation of the surfactant contained in the carbon fiber precursor treatment agent is unlikely to occur even when exposed to the carbon fiber precursor treatment temperature. In addition, when thermal runaway occurs due to thermal decomposition of the carbon fiber precursor, the endothermic reaction by the carbon fiber precursor treatment agent is likely to be insufficient. There is no mechanism to suppress the thermal runaway of the carbon fiber precursor, and problems such as fluffing, thread breakage, and fusion of fibers are likely to occur.
[0059] In the above-mentioned carbon fiber precursor treatment agent, there is no particular limitation on the mixing ratio of each component. From the viewpoint of suppressing adhesion between fibers and improving oil pick-up property in the carbon fiber precursor to which the treatment agent is applied, it is more preferable that the treatment agent contains 0.1 to 10 parts by mass of (B) polydimethylsiloxane, 5 to 50 parts by mass of (C) surfactant, and the remainder (D) water, relative to 100 parts by mass of (A) amino-modified silicone. The amount of each component can be appropriately adjusted depending on the desired particle size and stability of the emulsion, the properties of each component, and the like.
[0060] The carbon fiber precursor treating agent may have a total content of low molecular weight cyclic siloxanes (D4 to D6) in the carbon fiber precursor treating agent of 1000 ppm or less. In the present invention, it refers to components other than water (specifically, components (A), (B), and (C), and also includes additives such as preservatives and neutralizing acids when they are blended). Low molecular weight cyclic siloxanes of tetramers, pentamers and hexamers (also called D4, D5, D6) are volatile components and therefore cause contamination of the furnace in which the carbon fiber precursor is treated. Therefore, by making the total content of these components 1000 ppm or less, it is possible to obtain a carbon fiber precursor treating agent that causes less contamination of the furnace. The total content of low molecular weight cyclic siloxanes (D4 to D6) is more preferably 800 ppm or less, and even more preferably 500 ppm or less. A quantitative analysis can be performed by preparing a calibration curve for each low molecular weight cyclic siloxane. The concentration of the low molecular weight cyclic siloxane can be adjusted by a known method, for example, distillation of the raw material.
[0061] The present invention also provides a method for producing a carbon fiber bundle, comprising: a coating step of coating a carbon fiber precursor with the above-mentioned treating agent for carbon fiber precursor to obtain a treatment-adhered carbon fiber precursor; a flame-resistant step of flame-resistant treating the treatment-adhered carbon fiber precursor to obtain a flame-resistant fiber bundle; and a carbonization step of carbonizing the flame-resistant fiber bundle. The carbon fiber precursor treating agent according to the present invention is intended to be applied to the carbon fiber precursor to be subjected to the flame retardant treatment step, and may be applied to the carbon fiber precursor at any stage of the spinning process. It may be applied to the fiber bundle to be subjected to the drawing step, or may be applied at a stage after the drawing step. The number of times of application during the spinning process is not particularly limited.
[0062] The coating step is a step of coating the carbon fiber precursor with the carbon fiber precursor treatment agent to obtain a carbon fiber precursor with the treatment agent attached thereto. The amount of the carbon fiber precursor treatment agent attached to the carbon fiber precursor is preferably 0.1 to 2.0 mass%, more preferably 0.3 to 1.5 mass%. In the present invention, the amount of the carbon fiber precursor treatment agent attached refers to the amount of the active ingredient of the carbon fiber precursor treatment agent attached to the carbon fiber precursor, and the active ingredient of the carbon fiber precursor treatment agent refers to the components of the carbon fiber precursor treatment agent excluding water. In addition, the amount of the carbon fiber precursor treatment agent attached can be adjusted by adjusting the amount of the excess carbon fiber precursor treatment agent squeezed out after the carbon fiber precursor treatment agent is applied. The method of applying the treatment agent for carbon fiber precursors is not particularly limited, and can be a dipping foam method, a roller immersion method, etc. The liquid temperature of the tank storing the treatment agent for carbon fiber precursors is preferably in the range of 10 to 50° C. in order to suppress fluctuations in the concentration of the treatment agent for carbon fiber precursors and destruction of the emulsion. The amount of the active ingredient in the tank of the carbon fiber precursor treatment agent is preferably 0.01 to 10 mass%, more preferably 0.05 to 8 mass%. Usually, the silicone content is adjusted by appropriately diluting the carbon fiber precursor treatment agent containing 5 to 70 mass% of the active ingredient with water.
[0063] As the carbon fiber precursor used in the production method of the present invention, various precursors such as polyacrylonitrile (PAN), pitch, rayon (cellulose), etc. can be used. Polyacrylonitrile fiber bundles, which are easy to obtain the desired high-strength carbon fiber, can be preferably used.
[0064] The flame-retardant process is a process in which the carbon fiber precursor to which the treating agent for carbon fiber precursor is attached is flame-retardant-treated to obtain a flame-retardant fiber bundle. The flame-retardant process can be carried out under known conditions. For example, when PAN-based fibers are used as precursor fibers, the flame-retardant process is carried out in heated air at 200 to 260°C and at a draw ratio in the range of 0.85 to 1.15 for 10 to 100 minutes. This flame-retardant process causes a cyclization reaction in the fibers, and a flame-retardant fiber having an increased amount of oxygen bonded can be obtained. The flame-retardant process may be carried out by gradually increasing the process temperature using a temperature gradient.
[0065] The carbonization step is a step of carbonizing the flame-resistant fiber bundle by heating it to 300°C or higher in an inert atmosphere. Conventional known conditions can be adopted as the carbonization conditions. For example, a method of performing a first carbonization treatment at 300 to 800°C in a nitrogen atmosphere and then a second carbonization at 800 to 1600°C can be exemplified. When a higher elastic modulus is required, graphitization treatment may be performed at 2000 to 3000°C.
[0066] According to the method described above, adhesion (fusion and sticking) between fibers is suppressed, and the high oil pick-up property makes it possible to uniformly apply the treatment agent for carbon fiber precursors, thereby reducing oil adhesion to the equipment and gel formation in the tank, and therefore high-quality carbon fibers can be obtained with high production efficiency. EXAMPLES
[0067] In the following, examples will be given to more specifically explain the configuration and effects of the present invention, but the present invention is not limited to these examples. In the following examples and comparative examples, parts means parts by mass, and % means % by mass. All kinematic viscosities are measured at 25°C.
[0068] In the examples and comparative examples described below, amino-modified silicones having a linear siloxane skeleton, designated A1 to A4 below, were used. All of the amino groups in the amino-modified silicones used were of the 3-(2-aminoethylamino)propyl (-CH2-CH2-CH2-NH-CH2-CH2-NH2) type, and were attached only to the side chains of the siloxane skeleton. A1: Kinematic viscosity 200mm 2 It is an amino-modified silicone with an amine number of 0.25 meq / g and a terminal OH rate of 10%. A2: Kinematic viscosity 1000mm 2 It is an amino-modified silicone with an amine number of 0.6 meq / g and a terminal OH rate of 35%. A3: Kinematic viscosity 6000mm 2 It is an amino-modified silicone with an amine number of 0.15 meq / g and a terminal OH rate of 100%. A4: Kinematic viscosity 1000mm 2 It is an amino-modified silicone with an amine number of 0.1 meq / g and a terminal OH rate of 1%.
[0069] In the examples and comparative examples described below, polydimethylsiloxanes having linear siloxane skeletons, denoted as B1 to B5 below, were used. B1: Kinematic viscosity 100mm 2 / s, a polydimethylsiloxane with a ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals of 100 / 0. B2: Kinematic viscosity 400mm 2 / s, and is a polydimethylsiloxane with a ratio of SiOH groups / Si(CH3)3 at the molecular chain ends of 5 / 95. B3: Kinematic viscosity 2mm 2 / s, a polydimethylsiloxane with a ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals of 100 / 0. B4: Kinematic viscosity 1000mm 2 / s, a polydimethylsiloxane with a ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals of 100 / 0. B5: Kinematic viscosity 100mm 2 / s, and the ratio of SiOH groups / Si(CH3)3 at the molecular chain terminals is 1 / 99.
[0070] In the examples and comparative examples described below, the following nonionic surfactants C1 to C4 were used. C1: A nonionic surfactant in which 10 moles of ethylene oxide are added to an aliphatic alcohol having 12 carbon atoms. C2: A nonionic surfactant in which 200 moles of ethylene oxide are added to an aliphatic alcohol having 16 carbon atoms. C3: A nonionic surfactant in which 25 moles of ethylene oxide are added to an aliphatic alcohol having 16 carbon atoms. C4: A nonionic surfactant in which 5 moles of ethylene oxide are added to an aliphatic alcohol having 12 carbon atoms.
[0071] In the examples and comparative examples described below, ion-exchanged water was used as the water.
[0072] <Cyclic siloxane content measurement> The cyclic siloxane concentrations of D4 to D6 were measured using gas chromatography mass spectrometry under the following conditions. The measurement conditions were an injection temperature of 300°C, and a column temperature rise from 100°C to 300°C at a rate of 10°C / min, followed by a hold at 300°C for 40 minutes. The total contents of D4 to D6 are shown in Table 1.
[0073] <Thermogravimetric analysis> Thermogravimetric analysis was performed by placing approximately 1 mg of a sample on an aluminum sample dish, placing it in a thermogravimetric analyzer (Hitachi High-Tech Science EXSTAR 7000 Series TG / DTA 7300), and raising the temperature from room temperature (25°C) to 350°C at a heating rate of 5°C / min, and measuring the thermogravimetric curve (TG) of the sample. The sample was obtained by taking 10 g of the treatment agent for carbon fiber precursors, which is an oil-in-water silicone emulsion composition containing (A) to (D), heating and drying it at a temperature of 105°C for 3 hours, and then taking 1 mg. The TG obtained by thermogravimetric analysis was differentiated with respect to temperature to obtain a differential thermogravimetric curve (DTG) (the horizontal axis is temperature (℃) and the vertical axis is DTG (μg / min)). The DTG range from 150℃ to 300℃ was fitted with the function of equation (1), and T0 at that time was determined as the combustion peak temperature.
[0074] <Oil pickup evaluation method> 10,000 carbon fiber precursors with a thickness of 10 μm were cut into 20 cm lengths and their weight (referred to as w1) was measured. The fiber bundle was immersed in an oil bath in which the active ingredient was adjusted to a concentration of 0.2% using ion-exchanged water, and the water was squeezed out so that the total weight was 5 × w1. The wet carbon fiber precursor was placed in an oven at 105 °C for 3 hours to dry, and then the weight (referred to as w2) was measured. The oil pickup property was calculated as (w2-w1) / w1 × 100 (%).
[0075] The evaluation criteria for oil pick-up property are as follows. The pass standard is an evaluation result of B or higher, with A being more preferable. A: 1.0% or more B: 0.5 or more and less than 1.0% B - : 0.4 or more and less than 0.5% C: Less than 0.4%
[0076] <Adhesion evaluation method> 10,000 carbon fiber precursors with a thickness of 10 μm were cut into 20 cm lengths and their weights (referred to as w1) were measured. The fiber bundle was immersed in an oil bath in which the active ingredient was adjusted to a concentration of 0.2% using ion-exchanged water, and the water was squeezed out so that the total weight was 5 × w1. The flame-retardant treatment was performed under the conditions that the wet carbon fiber precursor was heated from 150 ° C to 250 ° C at a temperature increase rate of 5 ° C / min and then held at 250 ° C for 1 hour. The carbon fiber precursor was cut into 2 cm lengths, placed on black paper, and gently shaken to visually and microscopically observe the splitting state, and the splitting property was evaluated according to the following evaluation criteria.
[0077] The evaluation criteria for adhesion are as follows. Adhesion is a property that includes both fusion and sticking, and when both are suppressed, a rating of "A: no adhesion" or "B: almost no adhesion" is obtained. When either or both are not sufficiently suppressed, a rating of "C: much adhesion" is obtained. A rating of A or B is the pass standard. Adhesion Evaluation Criteria A: No adhesion B: Almost no adhesion C: Lots of adhesion
[0078] <Method for evaluating emulsion stability> The emulsion stability of the emulsion composition was evaluated by checking for oil floating as described below. Put 180g of ion-exchanged water into a 200ml plastic cup. Take 20g of the treatment agent with a dropper and stir it with the dropper until it is homogenous. Cover the plastic cup and leave it for 30 minutes. Remove the lid, illuminate the liquid surface with a fluorescent light, and visually observe the liquid surface. Prepare two samples. The evaluation criteria for oil floating are as follows: A: Nothing or one interference fringe of a few mm in size B: 2-3 interference fringes of a few mm in size C: Interference fringes of about 1 cm in size are visible. However, of the two samples, the one with the lower rating will be used.
[0079] <How to evaluate burn spots> 10,000 carbon fiber precursors with a thickness of 10 μm were cut into 20 cm lengths, and their weights (referred to as w1) were measured. The fiber bundles were immersed in an oil bath in which the active ingredient was adjusted to a concentration of 0.2% using ion-exchanged water, and the water was squeezed out so that the total weight was 5 × w1. The flame-retardant treatment was performed by heating the wet carbon fiber precursor from 150 ° C to 250 ° C at a heating rate of 5 ° C / min, and then holding it at 250 ° C for 1 hour. After removing the carbon fiber precursor from the oven, a 0.5 mm length was cut out with a sharp blade in the direction perpendicular to the fiber axis of the carbon fiber precursor, and the cross section of the single yarn was observed with a scanning electron microscope (SEM; JEOL JSM-IT100) at an accelerating voltage of 10 kV and a magnification of 1600 times.
[0080] The evaluation criteria for burn spots are as follows: Elemental line profiles are obtained in the diametric direction for 50 randomly selected cross sections of the carbon fiber precursor. If the element distribution varied within 5% from the center to the outside, it was judged as "no burn spots," but if there was a greater variation, it was judged as "burn spots present," and the number of each burn spot was counted. The evaluation criteria for each burnt spot count are as follows: Evaluation results are A to B - It is preferable that the formula is A or B. A:0 items B:1~2 items B - :3 items C: 4 or more
[0081] <Example 1> (A) 41 parts by mass of A1 as an amino-modified silicone, (B) 1 part by mass of B1 as a polydimethylsiloxane, and (C) 5 parts by mass of C1 as a surfactant were added with ion-exchanged water until the total amount reached 100 parts by mass, and the mixture was stirred with a homogenizer to prepare an oil-in-water emulsion, thereby obtaining a treatment agent for carbon fiber precursors. The measurement results and evaluation results of the treating agent for carbon fiber precursors are shown in Table 1 together with those of other examples and comparative examples. Extremely good results were obtained with respect to carbon fiber adhesion, oil pick-up, furnace contamination, and burn spots.
[0082] <Example 2> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that (B) polydimethylsiloxane B2 was used instead of B1. Extremely good results were obtained with respect to carbon fiber adhesion, oil pick-up, furnace contamination, and burn spots.
[0083] <Example 3> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that A2 was used instead of A1 as the (A) amino-modified silicone. Although the evaluation results were good, due to the characteristics of A2 having a high amine number, the DTG combustion peak was as high as 260°C, and the results were slightly inferior to Example 1 in terms of adhesion and burn spots. When the number of moles of ethylene oxide added to the nonionic surfactant is large, or when the number of amines or the terminal OH ratio of the amino-modified silicone is high, the DTG combustion peak temperature tends to be high.
[0084] <Example 4> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that A3 was used instead of A1 as the (A) amino-modified silicone. Although the evaluation results were good, the adhesion and burn spots were slightly inferior to those of Example 1 because the DTG combustion peak was as high as 250° C. due to the characteristics of A3, which has a high terminal SiOH ratio.
[0085] <Comparative Example 1> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that (B) polydimethylsiloxane B3 was used instead of B1. B3 had a low kinetic viscosity, so the oil pickup was somewhat poor. The main reason for the low oil pickup is thought to be that B3 did not adhere to the fibers. Most of the silicone that adhered to the fibers was thought to be A1, and therefore gelled quickly, causing sticking, resulting in poor adhesion evaluation results and noticeable burn spots.
[0086] <Comparative Example 2> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that (B) polydimethylsiloxane B4 was used instead of B1. In Comparative Example 2, adhesion was poor due to the occurrence of fusion, and burn spots were also significantly observed. B4 had poor emulsion stability due to its excessively high kinetic viscosity, and oil floated on the surface of the oil bath. As a result, it is believed that coating spots of the carbon fiber precursor treatment agent occurred on the surface of the carbon fiber precursor. It is believed that fusion occurred in areas where the oil agent was not applied, inducing burn spots.
[0087] <Comparative Example 3> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that (B) polydimethylsiloxane B5 was used instead of B1. In Comparative Example 3, adhesion was poor due to the occurrence of sticking, and burnt spots were also significantly observed. It is believed that B5 has a low ratio of SiOH groups / Si(CH3)3 at the molecular chain end, which resulted in poor compatibility between (A) and (B), and that the components were separated on the fiber. It is believed that sticking occurred at the amino group-rich site, which affected the evaluation of burnt spots.
[0088] <Comparative Example 4> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that 37 parts by mass of A1 was used as (A) the amino-modified silicone and 4 parts by mass of B1 was used as (B) the polydimethylsiloxane. In Comparative Example 4, the ratio of component (B) to component (A) was high, and the oil pickup was low because there was a lot of (B), which has low adsorption to fibers. Also, on the fibers, fusion occurred due to a lack of component (A), which has a fiber-protecting effect, and of course, burn spots occurred.
[0089] <Example 5> A carbon fiber precursor treatment agent was obtained in the same manner as in Example 1, except that A4 was used instead of A1 as the (A) amino-modified silicone. A4 has a low terminal SiOH ratio, so its crosslinking property is low and its fiber protection function is somewhat low. As a result, some fusion and burn spots were observed.
[0090] <Example 6> In Example 6, the amounts of components (A) to (D) are the same as in Example 1, but the ring-shaped body content is 5 parts by mass. The ring-shaped body also does not adsorb well to the fibers, so the oil pickup tends to be slightly lower. Also, on the fibers, fusion occurred due to a shortage of component (A), which has a fiber-protecting effect, and naturally, burnt spots occurred.
[0091] <Comparative Example 5> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 3, except that (B) polydimethylsiloxane was not blended. In Comparative Example 6, a highly adhesive gel was rapidly formed, causing sticking, resulting in a poor evaluation of adhesion and noticeable burn spots.
[0092] <Comparative Example 6> A treating agent for carbon fiber precursors was obtained in the same manner as in Example 1, except that components corresponding to components (A) and (B) were not mixed and only component (C) was used. In Comparative Example 7, since there was no silicone coating to protect the carbon fiber precursor, fusion occurred, resulting in a poor evaluation result for adhesion and noticeable burn spots.
[0093] <Example 7> (C) A treatment agent for carbon fiber precursors was obtained in the same manner as in Example 3, except that C2 was used instead of C1 as the surfactant. It is considered that the thermal runaway of the carbon fiber precursor was not completely suppressed because the combustion peak temperature of DTG was as high as 280°C, and slight fusion occurred. As a result, burn spots occurred.
[0094] <Example 8> (C) A treatment agent for carbon fiber precursors was obtained in the same manner as in Example 3, except that C3 was used instead of C1 as the surfactant. It is considered that the thermal runaway of the carbon fiber precursor was not completely suppressed because the combustion peak temperature of DTG was as high as 275°C, and slight fusion occurred. As a result, burn spots occurred.
[0095] <Example 9> (C) A treatment agent for carbon fiber precursors was obtained in the same manner as in Example 3, except that C4 was used instead of C1 as the surfactant. Since the peak combustion temperature of DTG is low at 175°C, the oil agent gelled quickly during flame retardation, which is thought to have caused slight sticking. This resulted in the occurrence of burnt spots.
[0096] [Table 1]
Claims
1. (A) an amino-modified silicone; (B) A kinematic viscosity at 25°C of 5 to 500 mm 2 / s, SiOH groups at molecular chain ends / Si(CH 3 ) 3 A polydimethylsiloxane having a ratio of from 3 / 97 to 100 / 0; (C) a surfactant; and (D) water, The content of the (B) component relative to 100 parts by mass of the (A) component is 0.1 parts by mass or more and 10 parts by mass or less, and the treating agent for carbon fiber precursors is an oil-in-water silicone emulsion composition.
2. The amino-modified silicone (A) has a SiOH group or a SiOCH 3 The treatment agent for carbon fiber precursors according to claim 1 , comprising 3% or more of an amino-modified silicone having a group.
3. 3. The treatment agent for a carbon fiber precursor according to claim 1, wherein the surfactant (C) is a nonionic surfactant.
4. The treatment agent for carbon fiber precursors according to any one of claims 1 to 3, characterized in that in a differential thermogravimetric curve (DTG) obtained by time-differentiating a thermogravimetric curve (TG) obtained by drying 1 mg of a sample of the treatment agent for carbon fiber precursors at a temperature of 105°C for 3 hours and heating the sample at a rate of 5°C / min with air circulation of 200 ml / min, a combustion peak is 180°C or higher and 270°C or lower.
5. The surfactant (C) is a nonionic surfactant having a polyoxyalkylene structure, The treatment agent for carbon fiber precursors according to any one of claims 1 to 3, wherein the average number of moles of oxyalkylene groups added in the surfactant (C) is adjusted so that a combustion peak in a differential thermogravimetric curve obtained by time-differentiating a thermogravimetric curve obtained when 1 mg of a sample obtained by drying the treatment agent for carbon fiber precursors at a temperature of 105°C for 3 hours is heated at 5°C / min with air circulation of 200 ml / min is within a range of -30°C or more and +20°C or less with respect to a preset carbon fiber precursor treatment temperature.
6. 100 parts by mass of the amino-modified silicone (A); 0.1 to 10 parts by mass of the polydimethylsiloxane (B); 5 to 50 parts by mass of the surfactant (C); The (D) water, The treating agent for carbon fiber precursors according to any one of claims 1 to 5, comprising:
7. The treatment agent for carbon fiber precursors according to any one of claims 1 to 6, wherein a total content of low molecular weight cyclic siloxanes (D4 to D6) in the treatment agent for carbon fiber precursors is 1000 ppm or less.
8. A coating step of coating a carbon fiber precursor with the treatment agent according to any one of claims 1 to 7 to obtain a carbon fiber precursor with the treatment agent attached thereto; a flame-retarding step of subjecting the treating agent-attached carbon fiber precursor to a flame-retardant treatment to obtain a flame-retardant fiber bundle; and a carbonization step of carbonizing the flame-resistant fiber bundle.
9. (A) an amino-modified silicone; (B) A kinematic viscosity at 25°C of 5 to 500 mm 2 / s, SiOH groups at molecular chain ends / Si(CH 3 ) 3 A polydimethylsiloxane having a ratio of from 3 / 97 to 100 / 0; (C) a nonionic surfactant; and (D) water; A treatment agent for carbon fiber precursors, which is an oil-in-water silicone emulsion composition comprising: The average number of moles of oxyalkylene groups added to the surfactant (C) is adjusted so that the combustion peak in a differential thermogravimetric curve obtained by time-differentiating a thermogravimetric curve obtained by drying 1 mg of a sample of the carbon fiber precursor treatment agent for 3 hours at a temperature of 105° C. and heating the sample at a rate of 5° C. / min with air circulation of 200 ml / min is within a range of −30° C. or more and 20° C. or less with respect to a preset carbon fiber precursor treatment temperature, A method for reducing burn spots in carbon fiber precursors.
Citation Information
Patent Citations
Method and device for detecting center position of article
JP1989088104A
Ornaments formed by utilizing optical fiber
JP1994086707A
Oil agent for production of carbon fiber
JP2001172879A
Synthetic fiber treating agent for producing carbon fiber and method for treating synthetic fiber for producing carbon fiber
JP2002129481A
Finishing oil for precursor for high performance carbon fibers and precursor
US5726241A
